Firms' Asset Holdings and Inflation Expectations - Saten Kumar (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2020)
This paper investigates the relationship between firms' inflation expectations and their holdings of liquid assets. We implement a new quantitative survey of firms' expectations about inflation in New Zealand. We find that firms that hold more shares of liquid assets systematically report lower inflation expectations. Moreover, we implement an experiment by providing firms new exogenous information about recent inflation dynamics. This experiment allows us to assess how firms respond to new information in terms of belief revisions and firm-level decisions.
Keywords: E2; E3; 330; liquid assets; illiquid assets; expectations; survey; inattention